Planting of pineapple using polyethylen cover - Botrel, Neide; Siqueira, Dalmo Lopes de; Couto, Flávio Alencar d'Araújo; Ramos, Victor Hugo Vargas (Pesquisa Agropecuaria Brasileira, 2014)
With the objective of reducing the damages caused by water deflciency in lhe pineapple plant, an assay was çonducted in Uberaba, MC, Brazil, employing a randomized block design in a two-factorial scheme, where the factors were: with, and without a polyethylene cover on the soil; spacings of 1,20 x 0,40 x 0,30 m and of 0,90 x 0,30 x 0,25 m; fertilization at 1/2 and 1/4 of basic level. It was observed that the average weights of the fruits with and without crown 'ere higher when the polyethylene cover was employed in combination with the spacing of 1,20 x 0,40 x 0,30 m, but without significant difference for the two levels of fertjlization. The averages for the content of total soluble solid compounds of the fruit, the average total acidity, the ratio between these variables and the fruit pil did not show any significant difference related to the experimental factors. The use of the polyethylene cover proved to be a recommendable means both for the increase of productivity and for avoiding the waste of fertilizer